Probe the Localized Electrochemical Environment Effects and Electrode Reaction Dynamics for Metal Batteries using In Situ 3D Microscopy. Issue 3 (16th December 2021) - Feng, Guangxia; Guo, Jiaming; Tian, Huajun; Li, Zhao; Shi, Yaping; Li, Xiaoliang; Yang, Xu; Mayerich, David; Yang, Yang; Shan, Xiaonan
Abstract: Uncontrollable dendrite growth is closely related to non‐uniform reaction environments. However, there is a lack of understanding and analysis methods to probe the localized electrochemical environment (LEE). Here the effects of the LEE are investigated, including localized ion concentrations, current density, and electric potential, on metal plating/stripping dynamics and dendrite minimization. A novel in situ 3D microscopy technique is developed to image the morphology dynamics and deposition rate of Zn plating/stripping processes on 3D Zn–Mn anodes. Using the in situ 3D microscope, the electrode morphology changes during the reactions are directly imaged and Zn deposition rate maps at different time points are obtained. It is found that reaction kinetics are highly correlated to LEE and electrode morphology. To further quantify the LEE effects, the digital twin technique is employed that allows the accurate calculation of the electrochemical environments, such as localized ion concentrations, current density, and electric potential, which cannot be directly measured from experiments. It is found that the curvature of the 3D electrode surface determines the LEE and significantly influences reaction kinetics. This provides a new strategy to minimize the dendrite formation by designing and optimizing the 3D geometry of the electrode to control the LEE. Abstract : The effect of the localized electrochemical environment (LEE) on metal batteries' reaction kinetics is studied by using novel in situ 3D microscopy and a digital twin technique. The LEEs, such as local current density, ion concentration, and potentials, are extracted. It is demonstrated that the LEE determines the localized reaction kinetics and the dendrite formation in 3D electrodes.